Development of sensorimotor organization guided by learning progress and predictability - Buğur, Serkan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
This thesis proposes an effective action parameter exploration mechanism that enables e cient discovery of robot actions through interacting with objects in a simulated table-top environment. For this, the robot organizes its action parameter space based on the generated e ects in the environment and learns forward models for predicting consequences of its actions. Following the Intrinsic Motivation approach, the robot samples the action parameters from the regions that are expected to yield high learning progress (LP). In addition to the LP-based action sampling, our method uses a novel parameter space organization scheme to form regions that naturally correspond to qualitatively di erent action classes, which might be also called action primitives. The proposed method enabled the robot to discover a number of lateralized movement primitives and to acquire the capability of prediction the consequences of these primitives. Furthermore, our ndings have some parallels with data from infant development, and might explain the reasons behind the earlier development of grasp compared to push action in infants, and the reasons behind the correspondence between development of action production and prediction.
Keywords: Computational learning theory.